Positivism, realism, and sources of law - Green, L (Cambridge University Press, 2021)
Taking the essential thesis of legal positivism to be that all law is positive law, that all law has sources, Green considers the relationships between legal positivism and ‘its closest cousin’, legal realism, focusing mainly on American legal realism. He looks at why legal realists disagree with legal positivists about the role of legal rules in explaining judicial decision-making. Noting that positivists and realists agree that law is constituted by social facts, that judges sometimes make law, and that law is morally fallible, he locates the point of disagreement in their different understandings of the boundary-lines between law and non-law. Green’s idea is that, unlike positivists, realists believe that a significant number of sources of law are only permissive sources – i.e. sources which judges are permitted, but not required, to use. These can sometimes be outweighed by considerations of policy, justice or the equities of the case, etc., which explains why realists can hold that law is so indeterminate as to undermine the causal efficacy of legal rules, while sharing the positivist view that all law has sources.